2020
DOI: 10.1103/physreve.101.020101
|View full text |Cite
|
Sign up to set email alerts
|

Manifolds in a high-dimensional random landscape: Complexity of stationary points and depinning

Abstract: We obtain explicit expressions for the annealed complexities associated respectively with the total number of (i) stationary points and (ii) local minima of the energy landscape for an elastic manifold with internal dimension d < 4 embedded in a random medium of dimension N ≫ 1 and confined by a parabolic potential with the curvature parameter µ. These complexities are found to both vanish at the critical value µc identified as the Larkin mass. For µ < µc the system is in complex phase corresponding to the rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…Further assuming the self-averaging property of this large determinant (4) we have obtained exact formulae for both these annealed complexities extending the known rigorous results [43,44] for gradient random field to fields with both gradient and solenoidal components. We have shown that the total complexity is independent of the fraction τ of gradient components while the complexity of stable equilibria undergoes an additional transition: it is negative for τ ≤ τ 0 (c) and positive conversely.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Further assuming the self-averaging property of this large determinant (4) we have obtained exact formulae for both these annealed complexities extending the known rigorous results [43,44] for gradient random field to fields with both gradient and solenoidal components. We have shown that the total complexity is independent of the fraction τ of gradient components while the complexity of stable equilibria undergoes an additional transition: it is negative for τ ≤ τ 0 (c) and positive conversely.…”
Section: Discussionsupporting
confidence: 54%
“…These properties can be exploited for the essential simplification in Kac-Rice formulae (16) reducing them after standard calculations, see e.g. [29,43], to the following form…”
Section: Definition Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…High-dimensional systems are typically associated to complex, highly non-convex energy landscapes, in which the number of stationary points (local minima, maxima or saddles) increases steeply with the dimensionality. Classifying these points in terms of their energy, of their stability and of their location in the underlying configuration space is a topic that is of interest in a large variety of fields, including disordered systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], ecology and biology [16][17][18][19], neural networks [20,21], inference [22][23][24][25][26], game theory [27], string theory and cosmology [28,29]. In many of these contexts, a crucial motivation for determining the distribution of stationary points is to understand how the energy functional is explored dynamically, through algorithms that proceed via local moves in configuration space, biased towards lower-energy configurations.…”
Section: Introductionmentioning
confidence: 99%
“…We remark that Fyodorov and Le Doussal also exhibited a quadratic/cubic near‐critical behavior for this model but in a different scaling, varying μ 0 for fixed B(0)$B^{\prime \prime }(0)$ and t 0 [31].…”
Section: Resultsmentioning
confidence: 99%